Syntheses, Evaluation and Characterization of Some 1, 3, 4-Oxadiazoles as Antimicrobial Agents - Niti Bhardwaj; S. K. Saraf; Pankaj Sharma; Pradeep Kumar (E-Journal of Chemistry)
1,3,4-Oxadiazoles show various biological activities and have been synthesized from different compounds. 1,3,4-oxadiazole is popularly known for its antimicrobial, anti-inflammatory, pesticidal and antihypertensive activities etc. It is well known that the synthesis of heterocyclic compounds tend to contain multi-structure in a molecule. The ring formation involves the condensation reaction. The challenge is to develop the ring system by incorporating the indole nucleus into it through the proposed reaction scheme. There are two free positions for the substitution in the oxadiazole ring system. In this study, it was planned to incorporate the oxadiazole ring system into indole ring. Synthesis of derivatives of 1,3,4-oxadiazoles from different benzaldehydes Characterization of the synthesized compounds along with their antimicrobial activity on different strains.